Treatment-Resistant Depression in Portugal - Bessa, João M. (2022)
Funding Information: SS is an employee of Janssen-Cilag Farmacêutica Lda. MF is an employee of CTI Clinical Trial and Consulting Services. The remaining authors received advisory board fees from Janssen-Cilag Farmacêutica Lda. AO-M was the national coordinator for Portugal of a non-interventional study EDMS-ERI-143085581, 4.0 to characterize a Treatment-Resistant Depression Cohort in Europe, sponsored by Janssen-Cilag, Ltd. 2019–2020; is the recipient of a grant from Schuhfried GmBH for norming and validation of cognitive tests; and is the national coordinator for Portugal of trials of psilocybin therapy for treatment-resistant depression, sponsored by Compass Pathways, Ltd. EudraCT numbers 2017-003288-36 and 2020-001348-25, and of esketamine for treatment-resistant depression, sponsored by Janssen-Cilag, Ltd. EudraCT Number: 2019-002992-33. Janssen had no influence on the interpretation of results. This manuscript presents the opinion of the psychiatry experts only. Funding Information: Support for third-party advisory board logistics and writing assistance, provided by CTI Clinical Trial and Consulting Services, was funded by Janssen-Cilag Farmacêutica Lda in accordance with Good Publication Practice (GPP3) guidelines. Publisher Copyright: Copyright © 2022 Bessa, Carvalho, Cunha, Fernandes, Matos-Pires, Neves, Oliveira-Maia, Santos and Santos.